WSGC NASA Internship Final Report - Rundle, Tessa (Proceedings of the Wisconsin Space Conference, 2017)
This report describes the activities carried out during a 10-week, full-time internship at NASA’s Johnson Space Center (JSC) in Houston, Texas. As an intern on the Space Suit Assembly (SSA) Development Engineering team, I contributed to several ongoing projects related to the advancement of Extravehicular Activity (EVA) space suits. Current EVA suits were designed for limited activities and usage time, and projected requirements of future exploration missions necessitate research into new suit components and materials. During my internship, I contributed mainly to the testing protocol for upcoming High-Performance EVA Glove (HPEG) testing, tasks for Z-2 suit testing, and studied the effects of radiation on space suit materials.